Вступительное слово - ЛюсинДмитрий Владимирович (Психология. Журнал Высшей школы экономики, 2014)
The emotions have always been a principle focus of study in psychological science.” A similar statement (a general and non-binding one) could be used to start an opening address to the special theme. However, if one gives it a little thought, it turns out that this assertion is rather controversial. In the old introspective psychology, emotions did receive much attention. However, in the early twentieth century. with the advent of behaviorism, the study of emotions became quite rare. (We mean the study of emotions by scientific psychology.) It is impossible to explore phenomena pertaining to the inner experience of man, with objective scientific methods. The only possibility was to study external manifestations of emotions, especially their physiological correlates, which could be used to determine the status of the body. Basically to this was the research of emotions limited in the absence of significant pro-motions in the theoretical understanding of affective phenomena. There was a revival of interest in the emotions with the advent of the psychology of neomentalism in the 1960s, which rediscovered an opportunity to study the inner world of man with scientific methods. At this time, theoretical reflections on the emotions came to life again and new research paradigms began to form. From then on an active development of the psychology of emotions has advanced. Formally, this is manifested by a substantial increase in publications, by new fields of research emerging, by new high-ranking scientific journals being published (e.g. Cognition & Emotion was started in 1987, Emotion — in 2001, Emotion Review — in 2009). The National Society for Research of Emotion was created between in 1984. April 2014 is the date for the inaugural conference of the Society for Affective Science, which aims to unite leading experts involved in the study of emotions within different disciplines. The development of the Russian psychology of emotions unfortunately still lags behind that of the rest of the world. On the whole there is not enough Russian psychological research into the emotions. However, some Russian authors follow modern standards of research, as evidenced by the proposed special issue. Here you can find works differing significantly in the subject, problems studied and methods used, but they represent a number of important areas of modern psychology of emotions. Briefly the areas of study are as follows: neurophysiological aspects of affective phenomena (articles by E.Mnatsakanyan et al. and R.Rozovskaya et al.); connection of affective and cognitive processes, including the specifics of processing emotional information and the impact of affective and cognitive processes at each other (articles by R.Rozovskaya et al., T.Sysoeva, A.Chetverikova et al., V.Ovsyannikova); the role of emotions in social interactions (articles by V.Ovsyannikova and A.Pankratova); affective processes in normal and pathological conditions (articles by E.Mnatsakanyan et al. and Yu.Chentsova-Dutton et al.); cultural specificity of human emotions (articles by Yu.Chentsova-Dutton et al.). Most authors represent different scientific institutions in Moscow and St. Petersburg. Yu.Chentsova-Dutton, an American psychologist by education and the workplace, is a native of Russia and maintains active scientific contacts with her Russian counterparts, thereby contributing to the development of the Russian psychology of emotions. This special issue is an attempt to present the current state of experimental psychology of emotions in Russia. A variety of themes and theoretical approaches of the research involved indicates a good potential that could lead to the development of Russia’s scientific psychology of emotions in the coming years.